PENGEMBANGAN INSTRUMEN PENILAIAN KEMAMPUAN KOMUNIKASI SAINS SEBAGAI BAGIAN DARI KETERAMPILAN ABAD 21 - Laifa Rahmawati; Jumadi Jumadi; Jaslin Ikhsan (Program Studi PGSD Universitas Flores, 2021)
Research has been carried out on the development of instruments for science communication skills as part of 21st Century skills at the higher education level. The instrument was developed from indicators of communication skills, namely understanding the key ideas of other people's utterances and presenting or reading data in the form of tables or graphs. The development carried out with the Borg and Gall model produces valid and reliable instruments. The test subjects were 94 students who were selected by cluster sampling. The tests carried out included construct validation tests, empirical validation tests, and testing the use of instruments to measure science communication skills. The results of construct validation show that the instrument is considered very good and suitable for use. The results of empirical validation show that the instrument is valid and reliable so that it can be used. The trial results show that the instrument for the assessment of the results of this development can be used to measure science communication skills.